STUDI CACAT BATANG PADA PRODUKSI KAYU JATI - Wesman Endom (Jurnal Penelitian Hasil Hutan, 2012)
This study excamined defects commonly encountered on teak logs. Defects are grouped into three categories, i.e. totaly bole, partial bole and minor defect. The study was conducted at three log collection center (IPK) in Cepu TPK Batokan, TPK Pasar Sore and TPK Cabak. Results showed that the average (%) of actual Hole Volume (HV) and Correction Value (CV) of mixed teak logs of three locations, were 18.28% (0.01-46.52%) and 0.82 (0.54-0.99). HV and CV values for were the partly holes grove of teak logs of those three locations 6.65% (0.01-23.82%) and 0.94 (0.76-0.99). The minor defect group of teak logs passessed HV and CK respectively 1.77% (0.06-14.86%) and 0.98 (0.85-0.99).